Looking through the mirror: representativeness of the Italian party system before the 2018 General Election - Beniamino Masi (QOE-IJES, 2021)
The use of the Internet and communication technologies has dramatically increased in recent times. This change has affected every aspect of political life, with electoral campaigns and parties making no exception. One of the most significant advancements on the theme is the spread of Voting Advice Applications (VAAs). These tools are developed before elections to match users’ policy preferences to those of the parties running. By looking at the dataset created with the answers of the users of an Italian VAA, Navigatore Elettorale, this study aims at understanding the representativeness of the six main parties running in the 2018 General Election. Through the development of a Representative Deficit Index, the study will also assess the key policy areas in which each of these parties performed best in the eyes of the electorate. The finding shows a diversified pattern of (in)successes for each of the parties, with some unexpected results.